Mission-critical Microsoft Exchange 2003 designing and building reliable exchange servers - Cochran, Jerry, 1964- (Amsterdam ; Boston : Elsevier Digital Press, 2004)
Mission-Critical Microsoft Exchange 2003 provides a complete update of Cochran's Mission-Critical Microsoft Exchange 2000, and complements Tony Redmond's new book, the best-selling Microsoft Exchange Server 2003. This book includes many of the same high-availability topics as the first edition but also expands the coverage of storage technology, server technology, management, and security. The book meets the needs of an Exchange administrator or system implementer who is striving to maintain a production Exchange environment that delivers superior service levels, high availability, manageability and scalability with the lowest cost of ownership. Gives "lessons learned" and other best practices from organizations that have successfully deployed Exchange Includes material on the forthcoming release of Exchange 2003 Offers advice from one of the most experienced storage practitioners.
Mission-Critical Exchange; Analyzing Downtime Outages; Exchange Database Technology Foundations; Exchange Disaster Recovery Technology; Exchange 2000 Disaster Recovery Best Practices; Leveraging Storage Technology; Leveraging Cluster Technologies for Exchange; Don't Overlook Security as a Powerful High-Availability Measure; Bringing It All Together With Proactive Management; Appendixes.
Includes bibliographical references and index.
Keywords: Microsoft Exchange server; Client/server computing; Electronic mail systems; Electronic books